Calcified extra-axial cavernous malformation arising from lower cranial nerves: A case report and literature review. Issue 5 (5th February 2021) - Ke, Daibo; Deng, Xueyun; Li, Xiang; Li, Jiuhong; Hui, Xuhui
Abstract: Rationale: Extra-axial cavernous malformations (ECMs) arising from cranial nerves (CNs) are rare. Complete "en bloc" lesion resection and hemosiderin-stained tissue preservation remain the standard treatment, while a different strategy may be needed when the lesion is highly calcified . We report the 3rd calcified ECM-CN and review the clinical features and surgical strategy for this rare condition considering previous literature. Patient concerns: We present a 52-year-old woman with a calcified lesion located in the right lower 1/3 of the cerebellopontine angle. Diagnosis: The diagnosis was calcified ECM-CNs according to the pathological and radiological features. Interventions: A posterior midline craniotomy was performed, and piecemeal resection of the lesion was carried out. Subtotal resection of the lesion was achieved with a small piece left in situ. Outcomes: No symptom or lesion-related recurrence was found during 28 months of follow-up. Lessons: Calcified ECM-CNs are unique cavernous malformations arising from CNs. Piecemeal resection and subtotal or near-total excision are 2 major aspects that differ from the surgical strategy for general ECM-CNs.